Korespondencja Krzesińskich 1856–1899 - Maria Wosiek (Pamiętnik Teatralny, 1976)
The author discusses and extensively quotes from letters written by the dancer Feliks Krzesiński, who settled in Saint Petersburg, to his actor brother Stanisław, who stayed in Poland and worked in provincial theatres. The manuscript collection (267 letters) is held at the Library of the Institute of Art, Polish Academy of Sciences. Apart from the bothers’ exchange, it includes several letters from Matylda Krzesińska the elder, one from Michał Chomiński, and some name day cards written by children. The correspondence mentions various figures from the world of dance, such as Jan Popiel, Barbara Jaworska, Julia, Józef, and Matylda Krzesiński, Marius Petipa, and Marianna Majewska. However, it documents not only ballet life, but also the social life of Polish emigres. The author of the article proposes a thematic categorisation of this epistolographic content: family matters, Russian theatre, Polish theatre, links between ballet and politics. She also discusses at length the economic reality of the period and supplies additional facts and contexts concerning the events described in the letters.